A Decision Support System for Irrigation Scheduling Using a Reduced-Size Pan - Georgios Nikolaou; Damianos Neocleous; Efstathios Evangelides; Evangelini Kitta (Agronomy)
An automatic, weight-based, small 20 cm diameter pan was used for real-time calculations of evaporation and precipitation in a semiarid environment. The water evaporated from the evaporimeter (EP) was found to be a significant predictor of evapotranspiration (ETO; r2 = 0.84), which was calculated with the Penman–Monteith (P-M) equation by retrieving climatic data from a weather station. The results revealed seasonal variations of the pan coefficient (KP; dimensionless), with a mean value estimated at 0.84 (±0.16). Validation of ETO measurements using a calibrated regression model (ETO = 0.831*EP + 0.025), against the P-M equation indicated a high correlation coefficient (r2 = 0.99, slope of the regression line of 0.9). The present paper evaluates and discusses the potential of using a reduced-size pan for real-time monitoring of water evaporation and precipitation, proposing an open-source irrigation decision support system.